Telehealth pada Kepatuhan Diet Pasien Penyakit Ginjal Kronis - Octaviani, Dinda Sesylia; Widyawati, Ika Yuni; Suarilah, Ira; Jannah, Fitriatul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to identify the effect of telehealth on diet compliance in CKD patients. The research method used systematic review sought relevant articles using MeSH-based keywords. Relevant full-text articles were retrieved from four databases: Scopus, PubMed, Science Direct, and ProQuest. Research guidelines followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The results showed that Telehealth programs can increase patient knowledge about the disease, treatment, laboratory results that show better results, and compliance. Telehealth interventions are promising avenues for CKD treatment delivery due to advances in technology and information. Telehealth programs may represent windows of opportunity, diet education, counselling with dieticians, sharing experience with others resulted improving patient’s knowledge on the disease, treatment, and compliance. Future telehealth programs that focus on developing the contents of telehealth modules based on evidence from this study. Keywords: Telehealth, Chronic Kidney Disease, Compliance, Health Service